It’s not the Fish that Stinks! EU Trade Relations with Morocco under the Scrutiny of the General Court of the European Union - Hummelbrunner, Sandra; Prickartz, Anne-Carlijn (Utrecht Journal of International and European Law, 2016)
The EU’s international agreements with Morocco on trade in agricultural and fishery products have drawn criticism due to their application to the disputed territory of Western Sahara, a territory that remains on the list of non-self-governing territories to be decolonised in accordance with the right of self-determination of the indigenous Sahrawi people. Recently, the Sahrawi liberation movement Front Polisario brought an action for annulment before the General Court of the European Union (GC) against the Council Decision approving the conclusion of one such agreement, alleging multiple violations of European and international legal norms. Interestingly, although the GC concurred by annulling the Decision insofar as it applies to Western Sahara, it chose to exclusively base its judgment on EU fundamental rights, invoking the EU’s failure to ensure that the fundamental rights of the Sahrawi people were not infringed by applying the agreements to Western Sahara. By summarily setting aside Front Polisario’s other claims, several relevant questions of applicable international and European law, which warrant further discussion, remain. This article examines these questions using the GC’s judgment in Front Polisario, thereby combining general matters of international and European law with the specific circumstances of the EU-Morocco relations and Western Sahara.